Determinasi Eksistensial Pemikiran Hukum Islam Abdullahi Ahmed An-Na`im - Tholkhatul Khoir (Islamica: Jurnal Studi Keislaman, 2014)
This article deals with the Islamic legal thought of Abdullahi Ahmed an-Naim from the sociology of knowledge approach. According to this approach, knowledge (including religious interpretation and practices) is sociologically, economically and politically determined. This article aims to understand how an-Naim's Islamic legal thought is determined by his existence within social reality. This article concludes that an-Naim's thought is determined by (1) socio-political and legal reality in Sudan, (2) Mahmoud Mohamed Taha who influenced his ideas, (3) British milieu, and (4) American environment which is politically secular, Islamo-phobic, racist, discriminative and intolerant towards Afro-Americans. The maturity of an-Na?im?s thought is particularly influenced by the history of British colonialism in Sudan and his academic training in England, a place where human rights discourse develops as the result of post-enlightenment humanism and some major revolutions in Europe.